2005
DOI: 10.1128/jcm.43.3.1234-1238.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Streptococcus canis Isolated from Milk of Dairy Cows with Subclinical Mastitis

Abstract: Streptococcus canis was isolated from 31 milk samples from 11 cows in a dairy herd (with 49 lactating cows) affected by subclinical mastitis in north Rhine-Westphalia, Germany. Thirty-one isolates from the infected udder quarters were further characterized for their phenotypic and molecular properties. Most isolates (83.9%) produced ␣-galactosidase, and all were negative for ␤-D-glucuronidase. Amplification of the 16S rRNA gene by the PCR method and digestion with the restriction enzymes RsaI, MspI, and AvaII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
56
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 29 publications
(39 reference statements)
11
56
1
2
Order By: Relevance
“…The antibiotic susceptibility patterns of S. canis isolates found in our study are generally in agreement with the findings of other authors (Wu et al 1997;Kataja et al 1998;Hassan et al 2005;Moyaert et al 2006). In addition, our rates of resistance to erythromycin and tetracycline are much lower than those reported by Wu et al (1997), who found 38.2% of strains resistant to erythromycin and 73.5% of strains resistant to tetracycline.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The antibiotic susceptibility patterns of S. canis isolates found in our study are generally in agreement with the findings of other authors (Wu et al 1997;Kataja et al 1998;Hassan et al 2005;Moyaert et al 2006). In addition, our rates of resistance to erythromycin and tetracycline are much lower than those reported by Wu et al (1997), who found 38.2% of strains resistant to erythromycin and 73.5% of strains resistant to tetracycline.…”
Section: Resultssupporting
confidence: 83%
“…On the other hand, Efstratiou et al (1994) described only 40% of strains as esculin positive and all positive reactions were reported as delayed, which might be responsible for some of the discrepancy. According to Hassan et al (2005) all S. canis isolates appeared to be esculin negative on primary culture; whereas, the isolates were uniformly positive after they were subcultured. This could be another potential source of variation.…”
Section: Resultsmentioning
confidence: 99%
“…equisimilis by biochemical and molecular tests (23)(24)(25). The analysis of 16S and 23S rRNA sequences and that of other housekeeping genes also allows the distinction between these two taxa (17,23) and shows a close genetic relationship of both to another beta-hemolytic streptococcal species, namely, Streptococcus pyogenes (Lancefield group A streptococcus [GAS]) (26). In-ter-and intraspecies differentiation of S. canis isolates may also be achieved by using various typing methods.…”
mentioning
confidence: 99%
“…This species has also been implicated in fetal or neonatal septicemia, leading to abortion or neonatal death, respectively (2,11), and in both canine and feline necrotizing fasciitis and streptococcal toxic shock syndrome (13,14). S. canis may be transmitted between different animal species living in proximity (15) and has been responsible for outbreaks of clinical and subclinical mastitis with bacterial shedding in milk in cattle herds (16,17) and in pets living in shelters (14). However, little is known about the genetic diversity of S. canis, namely, if there are clones particularly adapted to the different animal species.…”
mentioning
confidence: 99%
“…It is therefore strongly suggestive that the streptococcal isolates in this study are most likely S. canis. The studies of Clark et al (1984), Skyes et al (2005), Lyskova et al 2007b andLamm et al (2010) Hassan et al 2007). The Streptococcal isolates from this study were from the vagina swabs.…”
Section: Discussionmentioning
confidence: 99%